Facilitating a Web-Based Extensive Reading Course with “Edmodo” to Promote Students’ Proficiency in Reading - Rasyidah Nur Aisyah; Barotun Mabaroh (Universitas Pendidikan Mandalika, 2021)
Reading is a language skill that demands understanding. This understanding is determined by knowledge, experience, interest, and interest in a text. Based on the researcher's experience, most PGRI Wiranegara University students are less enthusiastic and have difficulty learning reading skills in English. The application of Edmodo as an E-Learning media is a personal microblogging-based learning medium that can be used to improve reading skills. The data source of this research is the fifth-semester students of the English Education study program at PGRI Wiranegara University. The research data were obtained from observations, tests, documentation, and student questionnaires. The results showed that the application of Edmodo as an E-Learning media could be applied to independent learning of reading skills. Besides that, it is also a medium that can connect lecturers and students to communicate outside the campus. Analysis of student test results shows that students have reached an average score of 87, which means they have met the minimum completeness standards. Based on the results of the questionnaire, learning through Edmodo can motivate students to practice reading skills. Based on the results of this study, it can be concluded that the application of Edmodo as an E-Learning media has been successfully applied to reading skills in learning English. In addition, Edmodo can also be applied to other language skills besides reading skills.